Identification of Characteristics in Very Small Entities to Implement DevOps: Determining Strengths and Opportunities for Improvement - Pastrana-Pardo, Manuel-Alejandro; Ordoñez-Erazo, Hugo-Armando; Cobos-Lozada, Carlos-Alberto (Revista Científica, 2024)
Using frameworks such as Scrum and DevOps has transformed companies’ software development process, increased their quality, facilitated early feedback, and automated repetitive activities through tools to reduce reprocessing, monitor various elements, and enable faster production deployment. However, their implementation requires significant effort, as these frameworks clearly express what can be done but not how. Consequently, discovering which practices, techniques, and tools can be implemented becomes a matter of trial and error, which is very costly for companies of limited size, such as those called very small entities (VSEs), consisting of up to 25 employees according to the ISO/IEC 29110 norm. Therefore, this article proposes a set of questions that help determine the current state of companies regarding the implementation of the practices suggested by DevOps, helping to identify which specific aspects can be improved. Additionally, the proposal was evaluated use by seven companies to determine the feasibility of its use by seven companies to determine its feasibility. The application of the questions highlighted the importance of understanding a company's strengths and opportunities for improvement to design a successful implementation guide for the practices mentioned above.